2021
DOI: 10.1055/s-0041-1726278
|View full text |Cite
|
Sign up to set email alerts
|

Does Microalbuminuria Predict Mortality in Pediatric Intensive Care Unit?

Abstract: The aim of this study is to assess the accuracy of microalbuminuria (MA) to predict the mortality in pediatric intensive care unit (PICU). Between December 2014 and November 2015, 250 patients who were 1 month to 18 years old monitored at least 24 hours in PICU and met study criteria were included. Spot urine samples were measured for microalbuminuria. Pediatric Risk of Mortality III-24 and Pediatric Multiple Organ Dysfunction scores were calculated by using the worst parameters in first 24 hours. The collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Akbas et al . found PICU patients who were hyperphosphataemic on admission had a significantly higher Paediatric Logistic Organ Dysfunction score and higher mortality 10 . Given that phosphate is well absorbed via the enteral route and minimises the complications arising from IV administration, supplementation by the enteral route has been suggested in children with mild or moderate deficits 23 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Akbas et al . found PICU patients who were hyperphosphataemic on admission had a significantly higher Paediatric Logistic Organ Dysfunction score and higher mortality 10 . Given that phosphate is well absorbed via the enteral route and minimises the complications arising from IV administration, supplementation by the enteral route has been suggested in children with mild or moderate deficits 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory reference range for serum phosphate was 1.0–2.5 mmol/L for infants aged 0–1 years and 1.0–2.0 mmol/L for children aged 1–2 years. Additional phosphate can be given by enteral supplementation or prescription adjustments for children receiving tailor‐made intravenous (IV) nutrition but phosphate supplementation and hyperphosphataemia also bring risks 10 . Our usual practice therefore was not to initiate phosphate supplementation unless serum phosphate was <0.7 mmol/L.…”
Section: What Is Already Known On This Topicmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, an occurrence rate of hypophosphatemia in critically ill children varying from 5% to 76% has been reported, depending on the cut-off value used [11]. Moreover, the consequences of hypophosphatemia remain uncertain, although some studies have reported an association between hypophosphatemia and worse clinical outcome in critically ill children [2,5,7,9,10].…”
Section: Introductionmentioning
confidence: 99%